2012
DOI: 10.1007/s00345-012-0902-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating free testosterone is an independent predictor of advanced disease in patients with clinically localized prostate cancer

Abstract: Low pre-treatment fT levels were significantly associated with tumour stage and extraprostatic tumour spread and might-in addition or combination with PSA-serve as a useful prognostic parameter for prostate cancer patients prior to radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
4
29
4
Order By: Relevance
“…In addition, obese patients presented more often with higher pathological tumour stage (p = 0.027, Chi-square). Similar results were found for patients with a WC > 110 cm who also suffered significantly more often from aggressive PC (Gleason score ≥ 8 vs. [2][3][4][5][6][7]19.0 vs. 10.7 %, p = 0.006, Fisher's exact), nodal metastasis (12.5 vs. 7.2 %, p = 0.039, Fishers' exact), and-by tendency-higher tumour stages (p = 0.12, Chi-square). However, the surgical margin status did not correlate with a high BMI or large WC.…”
Section: Association Between Obesity and Tumour Stage/gradesupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, obese patients presented more often with higher pathological tumour stage (p = 0.027, Chi-square). Similar results were found for patients with a WC > 110 cm who also suffered significantly more often from aggressive PC (Gleason score ≥ 8 vs. [2][3][4][5][6][7]19.0 vs. 10.7 %, p = 0.006, Fisher's exact), nodal metastasis (12.5 vs. 7.2 %, p = 0.039, Fishers' exact), and-by tendency-higher tumour stages (p = 0.12, Chi-square). However, the surgical margin status did not correlate with a high BMI or large WC.…”
Section: Association Between Obesity and Tumour Stage/gradesupporting
confidence: 86%
“…Ever since, there are controversies in the literature about the relationship between both high and low sex hormone serum levels, such as testosterone or estradiol and their involvement in the formation of aggressive localized PC [6,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese men have been shown to exhibit reduced levels of androgens (51), and there is evidence that men with lower levels of testosterone have more aggressive tumors at clinical presentation (52,53). The influence of early-life exposures is suspected to be important in prostate cancer etiology (13) as carcinogenic processes have been seen within prostatic tissue in men in their 20s (14).…”
Section: Articlementioning
confidence: 99%
“…After initiation of hormone therapy, however, serum testosterone and intraprostatic levels of DHT have been shown to become positively correlated [10]. Interestingly, two recent studies [11,12] have found a positive correlation between percentage-free testosterone (measured as free testosterone/total testosterone) and high-grade features on either biopsy or final prostatectomy.…”
Section: Basis For Androgen Ablation As a Treatment For Prostate Cancermentioning
confidence: 93%